2016
DOI: 10.11114/jets.v4i4.1254
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Solution Focused Group Counseling for High School Students in Order to Struggle with School Burnout

Abstract: In this research, the effect of solution focused group counseling upon high school students" struggling with school burnout was analyzed. The research was an experimental study in which a pre-test post-test control group random design was used, depending upon the real experimental model. The study group included 30 students that volunteered from among students studying at a high school in central Erzincan Province in the 2014-2015 academic year. School Burnout Scale (Seç er, Halmatov, Veyis and Ateş, 2013) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 32 publications
(35 reference statements)
0
11
0
6
Order By: Relevance
“…In practice, the medical center can use different types of approaches to help medical staff improve stress, pain, and illness, such as mindfulness-based stress reduction (MBSR) programs, "positivity currency", "appreciative inquiry" groups , cognitive behavioral therapy (Gustafsson et al, 2017), rational emotive behavior counseling (Kim & Yoon, 2018), solution focused brief counseling (Ateş, 2016), and many other therapies. When high burnout employees are found, hospital management can initiate the above approaches to reduce their resilience.…”
Section: Discussionmentioning
confidence: 99%
“…In practice, the medical center can use different types of approaches to help medical staff improve stress, pain, and illness, such as mindfulness-based stress reduction (MBSR) programs, "positivity currency", "appreciative inquiry" groups , cognitive behavioral therapy (Gustafsson et al, 2017), rational emotive behavior counseling (Kim & Yoon, 2018), solution focused brief counseling (Ateş, 2016), and many other therapies. When high burnout employees are found, hospital management can initiate the above approaches to reduce their resilience.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there are experiment-oriented group studies based on sbfa. For example, in the six-session group study based on sbfa by Ateş (2016), it reduced students' burnout levels. In the study by İşlek (2006), it was found that the sbfa -based group study had an effect on alleviating the text anxiety experienced by students preparing themselves for the university entrance exam.…”
Section: Discussionmentioning
confidence: 99%
“…Dahası olumsuz aile tutumlarının çocuklar üzerinde stres oluşturabildiği öğrencilerde yorgunluk, gerginlik ve tükenmişliğe neden olabileceği söylenmektedir (Aypay, 2011). Alanyazında yer alan okul tükenmişliğini önlemeye yönelik doğrudan çocuklara yönelik uygulamalar yapıldığı görülmektedir (Ateş, 2016). Bu araştırma aile ilişkilerinin de okul tükenmişliğini açıklamada önemli bir değişken olduğu sonucuna ulaşılmıştır.…”
Section: Tartışma Sonuç Ve öNerilerunclassified
“…Okul tükenmişliği eğer önlem alınmazsa, okul terki (Bask ve Salmela-Aro, 2013), akademik başarısızlık (Bilge vd., 2014;May vd., 2015), düşük özgüven (Virtanen vd., 2016) ve depresyon (Walburg, 2014) gibi farklı sorunlara neden olabilmektedir. Bu sebeple son dönemlerde okullarda öğrencilerin yaşamış oldukları tükenmişlik ve nedenlerinin neler olduğu araştırılıp (May vd., 2015), bu konuda çeşitli önleyici çalışmalar yapılmaktadır (Ateş, 2016). Okul tükenmişliği de yetişkinlerin yaşamış olduğu tükenmişlik gibi stres veren yaşantılar sonucunda ortaya çıkmaktadır (Seibert vd., 2016).…”
Section: Introductionunclassified